PERAN PERCEIVED QUALITY MEMEDIASI PRICE DENGAN PERCEIVED VALUE - Agustini, Ni Kmg; Sukawati, Tjok Gede Raka (E-Jurnal Manajemen; Vol 6 No 6 (2017), 2017)
This research was conducted with the aim of explaining the effect of variable price (the price) and perceived quality (perceived quality) of the perceived value (perception niali), as well as the role of perceived quality (perceived quality) in mediating the effects of price (the price) of the perceived value (perceived value). The method used to determine the sample is non-probability sampling form of purposive random sampling with a sample size of 77 respondents. The data collection is done by distributing questionnaires directly in Denpasar and Badung. Data analysis techniques used adalan Partial Least Square (PLS). The results showed that the price (the price) significant and positive impact on the perceived quality (perceived quality) and berepengaruh significantly and positively to the perceived value (perceived value), as well as the perceived quality (perceived quality) significant and positive impact on the perceived value (perception niali) and positive and significant effect on the price (the price). Perceived quality (perceived quality) play a significant role in mediating the relationship between price (the price) and perceived value (perceived value).
Keywords: price (the price), perceived quality (perceived quality), perceived value (perceived value